Morphological trait matching shapes plant–frugivore networks across the Andes - Bender, Irene Maria Antoinetta (2018)
Interactions between resource and consumer species are organized in ecological networks. Species interactions in these networks are influenced by the functional traits of the interacting partners, but the generality of trait-based interaction rules and the relationship between functional traits and a species’ specialization on specific interaction partners are not yet understood. Here we combine data on eight interaction networks between fleshy-fruited plants and frugivorous birds sampled across the tropical and subtropical Andean range. We test which combinations of morphological plant and animal traits determine trait matching between resource and consumer species in these networks. In addition, we test which of the morphological traits influence functional specialization of plant and bird species. In a meta-analysis across network-specific fourth-corner analyses, we found that plant–animal trait pairs related to size matching (fruit size–beak size) and avian foraging behavior (plant height–wing shape and crop mass–body mass) were positively related in these networks. The degree of functional specialization on specific interaction partners was positively related to crop mass in plants and to the pointedness of the wing in birds. Our findings show that morphological trait matching between fleshy-fruited plants and frugivorous birds is a general phenomenon in plant–frugivore networks across the Andes and that specific plant and bird traits can be used to approximate the degree of functional specialization. These insights into the generality of interaction rules are the base for predictions of species interactions in ecological networks, for instance in novel communities in the future, and can be applied to identify plant and animal species that fulfill specialized functional roles in ecological communities.